Is oral-dental health training in faculties of medicine and dentistry sufficient? A comparison of students' knowledge levels - Zahide Koşan; Nilgün Akgül; Banu Bedir; Elif Okşan Çalıkoğlu; Sinan Yılmaz; Sera Şimşek Derelioğlu (Turkish Society of Public Health Specialists, 2017)
Objective: Awareness of oral-dental health needs to be improved, disseminated and maintained due to the frequent occurrence of dental problems in Turkish society. The purpose of this study was to determine the level of oral-dental health knowledge among Medical and Dentistry Faculty students. This was deemed especially pertinent as these students will be responsible for propagating higher levels of awareness and assisting activities aimed at overcoming the deficiencies identified.  Method: 247 clinically active students at the Erzurum Atatürk University, Faculties of Medicine and Dentistry participated in this descriptive study. Data was collected via a questionnaire. Participants' demographic data were recorded and their knowledge of oraldental health was measured. Results: Males represented 55.9% of the participants in the study. Students' mean age was 24.7±1.9 years; 46.2% were dental faculty students and 53.8% medical faculty students. Levels of correct responses to questions concerning oral-dental health among medical faculty students ranged between 4.5% and 66.9%, while those of dental faculty students ranged between 29.8% and 97.4%. Significant variation in information levels was observed between dental and medical faculty students (p<0.05). Conclusions: Although the oral-dental health knowledge among the future dentists was generally adequate, basic knowledge among the future physicians was not generally at an adequate level. It would therefore be useful for medical faculties to add oral-dental health to pre-graduation training. Key words:  Oral-dental health, medical training, levels of knowledge of oral-dental health